Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.

Formulario derivadas e integrales[1]

1,627 views

Published on

Published in: Education
  • Be the first to comment

Formulario derivadas e integrales[1]

  1. 1. Tabla de derivadas1. D x (u n ) = nu n −1 D x u2. D x (u + v) = D x u + Dx v3. D x (uv) = uD x v + vD x u  u  vD u − uD v4. D x   = x 2 x v v5. D x (e ) = e D x u u u6. D x ( a u ) = a u ln a D x u 17. D x (lnu ) = D x u u8. D x ( sen u ) = cos u D x u9. D x (cos u ) = − sen u D x u10. D x (tan u ) = sec 2 u D x u11. D x (cot u ) = − csc 2 u D x u12. D x (sec u ) = sec u tan u D x u13. D x (csc u ) = − csc u cot u D x u 114. D x (arcsen u ) = Dxu 1 − u2 −115. D x (arccos u ) = Dx u 1 − u2 116. D x (arctan u ) = Dx u 1 + u2 −117. D x (arc cot u ) = Dx u 1 + u2 118. D x ( arc sec u ) = Dx u u u2 − 1 −119. D x ( arc csc u ) = Dx u u u2 −120. D x ( senh u ) = cosh u D x u21. D x (cosh u ) = senh u D x u22. D x (tanh u ) = sec h 2 u D x u23. D x (coth u ) = − csc h 2 u D x u24. D x (sec h u ) = − sec h u tanh u D x u25. D x (csc h u ) = − csc h u coth u D x u
  2. 2. Tabla de integralesFormas elementales 1. ∫ du = u + c 2. ∫ a du = au + c 3. ∫ [ f (u ) + g (u )]du = ∫ f (u )du + ∫ g (u )du u n +1 ∫ u du = +c (n ≠ 1) n 4. n +1 du 5. ∫ u = ln u + cFormas racionales que contienen a + bu ∫ a + bu = b [a + bu − a ln a + bu ] + c u du 1 6. 2 u 2 du 1  1  7. ∫ = 3  (a + bu ) − 2a (a + bu ) + a 2 ln a + bu +c 2 a + bu b  2  u du 1  a  8. ∫ = 2 + ln a + bu  + c (a + bu )2 b  a + bu  u 2 du  1 a2  9. ∫ (a + bu ) 2 =   a + bu − b3 a + bu − 2a ln a + bu  + c  u du 1  a 1  10. ∫ (a + bu ) 3 = 2 b  2(a + bu ) 2 − +c a + bu  du 1 u 11. ∫ u(a + bu ) = a ln a + bu +c du 1 b a + bu 12. ∫ u (a + bu ) = − au + a 2 2 ln u +c du 1 1 u 13. ∫ u(a + bu ) 2 = + 2 ln a(a + bu ) a a + bu +cFormas que contienen a + bu 2 (3bu − 2a )(a + bu ) 2 + c 3 14. ∫u a + bu du = 15b 3
  3. 3. 15. ∫ u 2 a + bu du = 2 3 ( ) 15b 2 u 2 − 12abu + 8a 2 (a + bu ) 2 + c 3 105b 2u n (a + bu ) 2 3 2an 16. ∫ u a + bu du = u n −1 a + bu du b(2n + 3) ∫ n − b(2n + 3) = 2 (bu − 2a ) a + bu + c u du 2 17. ∫ a + bu 3b 18. ∫ u 2 du = 2 ( 3b 2 u 2 − 4 abu + 8 a 2 ) a + bu + c a + bu 15 b 3 u n du 2u n a + bu 2an u n −1 du 19. ∫ a + bu = b(2n + 1) − b(2n + 1) ∫ a + bu 1 a + bu − a ln +c si a > 0 du a a + bu + a 20. ∫ = u a + bu 2 a + bu arctan +c si a < 0 −a −a du a + bu b(2n − 3) du 21. ∫u n a + bu =− a(n − 1)u n −1 − 2a(n − 1) ∫ u n − 1 a + bu a + bu du du 22. ∫ u = 2 a + bu + a ∫ u a + bu a + bu du (a + bu ) 2 b(2n − 5) a + bu du 3 23. ∫ u n =− a (n − 1)u n −1 − 2a (n − 1) ∫ u n −1Formas que contienen a 2 ± u 2 du 1 u 24. ∫a 2 +u 2 = arctan + c a a 1 u arctan h + c si u < a du 1 u+a a a 25. ∫ 2 = ln +c= a −u 2 2a u − a 1 u arc coth + c si u > a a a
  4. 4. 1 u − arctan h + c si u < a du 1 u−a a a 26. ∫ 2 = ln +c= u −a 2 2a u + a 1 u − arc coth + c si u > a a aFormas que contienen u2 ± a2En las fórmulas 27 a 38 se puede sustituir (ln u + u 2 + a 2 ) por u arcsenh a uln u + u 2 − a 2 por arccos h a a + u2 + a2 aln por arcsenh u u du 27. ∫ u ±a2 2 = ln u + u 2 ± a 2 + c u a2 28. ∫ u ± a du = 2 u ±a ± 2 2 2 ln u + u 2 ± a 2 + c 2 2 u 29. ∫ u 2 u 2 ± a 2 du = 2u 2 ± a 2 u 2 ± a 2 − 8 ( a4 8 ) ln u + u 2 ± a 2 + c u 2 + a 2 du a + u2 + a2 ∫ = u + a − a ln +c 2 2 30. u u u 2 − a 2 du u 31. ∫ u = u 2 − a 2 − a arc sec a +c u 2 ± a 2 du u2 ± a2 32. ∫ u2 =− u + ln u + u 2 ± a 2 + c u 2 du u 2 ± a2 33. ∫ u2 ± a2 = 2 u ± a2 − 2 ln u + u 2 ± a 2 + c 1 a+ u +a 2 2 du 34. ∫ = − ln +c u u2 + a2 a u du 1 1 35. ∫u u2 − a2 = a arc sec + c a du u2 ± a2 36. ∫u 2 u2 ± a2 =− ± a 2u +c
  5. 5. ∫ (u ) ( ) 3 u 3a 4 37. 2 ± a2 2 du = 2u 2 ± 5a 2 u2 ± a2 + ln u + u 2 ± a 2 + c 8 8 du u 38. ∫ = +c (u ) 3 2 ±a 2 2 ± a2 u2 ± a2Formas que contienen a2 − u2 du u 39. ∫ a −u 2 2 = arcsen a +c u a2 u 40. ∫ a 2 − u 2 du = 2 a2 − u2 + 2 arcsen + c a a 2 − u 2 du = (2u 2 − a 2 ) a 2 − u 2 + u a4 u 41. ∫ u 2 arcsen + c 8 8 a a 2 − u 2 du a + a2 − u2 a ∫ = a − u − a ln + c = a 2 − u 2 − a arccos h +c 2 2 42. u u u a 2 − u 2 du u a2 − u2 43. ∫ u 2 u a =− +c − arcsen u 2 du u a2 u 44. ∫ a −u 2 2 =− 2 a2 − u2 + 2 arcsen + c a 1 a+ a −u 2 2 du 1 a 45. ∫ = − ln + c = − arccos h + c u a −u 2 2 a u a u du a2 − u2 46. ∫u 2 a2 − u2 =− a 2u +c ∫ (a − u 2 ) 2 du = − (2u 2 − 5a 2 ) a 2 − u 2 + 3a arcsen u + c 4 2 3 u 47. 8 8 a du u 48. ∫ = +c (a ) a2 − u2 3 2 −u 2 2 a2Formas que contienen 2au − u 2 u−a a2  1 49. ∫ 2au − u 2 du = 2 2au − u 2 + u arccos 1 −  + c  a 2u − au − 3a 2 2 a 3  u 50. ∫ u 2au − u 2 du = 2au − u 2 + arccos 1 −  + c 6 2  a 2au − u 2 du  u 51. ∫ u = 2au − u 2 + a arccos 1 −  + c  a
  6. 6. 2au − u 2 du 2 2au − u 2  u 52. ∫ u 2 u =− − arccos 1 −  + c  a du  u 53. ∫ 2au − u 2 = arccos 1 −  + c  a u du  u 54. ∫ 2au − u 2 = − 2au − u 2 + a arccos 1 −  + c  a u 2 du (u + 3a ) 3a 2  u 55. ∫ 2au − u 2 =− 2 2au − u 2 + 2 arccos 1 −  + c  a du 2au − u 2 56. ∫u 2au − u 2 =− au +c du u−a 57. ∫ = +c (2au − u ) 3 2 2 a 2 2au − u 2 u du u 58. ∫ = +c (2au − u ) 3 2 2 a 2au − u 2Formas que contienen funciones trigonométricas 59. ∫ sen u du = − cos u + c 60. ∫ cos u du = sen u + c 61. ∫ tan u du = ln sec u + c 62. ∫ cot u du = ln sen u + c 63. ∫ sec u du = ln sec u + tan u + c = ln tan ( π + u ) + c 1 4 1 2 64. ∫ csc u du = ln csc u − cot u + c = ln tan u + c 1 2 65. ∫ sec u du = tan u + c 2 66. ∫ csc u du = − cot u + c 2 67. ∫ sec u tan u du = sec u + c 68. ∫ csc u cot u du = − csc u + c 1 1 ∫ sen u du = u − sen 2u + c 2 69. 2 4 1 1 70. ∫ cos 2 u du = u + sen 2u + c 2 4 71. ∫ tan u du = tan u − u + c 2 72. ∫ cot 2 u du = − cot u − u + c
  7. 7. 1 n −1 73. ∫ senu du = − sen n − 1 u cos u + n n−2 ∫ sen u du n n 1 n −1 n −1 n−2 74. ∫ cos u du = cos u sen u + n ∫ cos u du n n 1 75. ∫ tan n u du = tan n − 1 u − ∫ tan n − 2 u du n −1 1 n −1 n−2 ∫ cot u du = − n − 1 cot u − ∫ cot u du n 76. 1 n−2 n−2 n−2 ∫ sec u du = n − 1 sec u tan u + n − 1 ∫ sec u du n 77. 1 n−2 n−2 n−2 ∫ csc u du = − n − 1 csc u cot u + n − 1 ∫ csc u du n 78. sen (m + n )u sen (m − n )u 79. ∫ sen mu sen nu du = − 2(m + n ) + 2(m − n ) + c sen (m + n )u sen (m − n )u 80. ∫ cos mu cos nu du = 2(m + n ) + 2(m − n ) + c cos (m + n )u cos (m − n )u 81. ∫ sen mu cos nu du = − 2(m + n ) − 2(m − n ) + c 82. ∫ u sen u du = sen u − u cos u + c 83. ∫ u cos u du = cos u + u sen u + c 84. ∫ u 2 sen u du = 2u sen u + (2 − u 2 )cos u + c 85. ∫ u 2 cos u du = 2u cos u + (u 2 − 2 ) sen u + c 86. ∫ u n sen u du = −u n cos u + n ∫ u n − 1 cos u du 87. ∫ u n cos u du = u n sen u − n ∫ u n − 1 sen u du sen m − 1 u cos n + 1 u m − 1 m−2 88. ∫ sen u cos u du = m n + ∫ sen u cos u du n m+n m+n sen m + 1 u cos n − 1 u n −1 n−2 = + ∫ sen u cos u du m m+n m+nFormas que contienen funciones trigonométricas inversas ∫ arcsenu du = u arcsenu + 1 − u + c 2 89. 90. ∫ arccos u du = u arccos u − 1 − u + c 2 91. ∫ arctan u du = u arctan u − ln 1 + u + c 2
  8. 8. 92. ∫ arc cot u du = u arc cot u + ln 1 + u 2 + c 93. ∫ arc sec u du = u arc sec u − ln u − u2 − 1 + c = u arc sec u − arccos h u + c 94. ∫ arc csc u du = u arc csc u + ln u + u2 − 1 + c = u arc csc u + arccos h u + cFormas que contienen funciones exponenciales y logarítmicas 95. ∫ e u du = e u + c au 96. ∫ a u du = +c ln a 97. ∫ ue u du = e u (u − 1) + c 98. ∫ u n e u du = u n e u − n ∫ u n − 1e u du u nau n 99. ∫ u n a u du = u n − 1 a u du ln a ∫ − ln a e u du eu 1 e u du 100. ∫ n = − (n − 1)u n − 1 n − 1 ∫ u n − 1 + u a u du au ln a a u du 101. ∫ un =− (n − 1)u n − 1 n − 1 ∫ u n − 1 + 102. ∫ ln u du = u ln u − u + c un +1 103. ∫ u n ln u du = [(n + 1) ln u − 1] + c (n + 1)2 du 104. ∫ u ln u = ln ln u + c e au 105. ∫ e au sen nu du = (a sen nu − n cos nu ) + c a2 + n2 e au 106. ∫ e au cos nu du = (a cos nu + n sen nu ) + c a2 + n2Formas que contienen funciones hiperbólicas 107. ∫ senh u du = cosh u + c
  9. 9. 108. ∫ cosh u du = senh u + c109. ∫ tanh u du = ln cosh u + c110. ∫ coth u du = ln senh u + c111. ∫ sec h u du = arctan (senh u ) + c112. ∫ csc h u du = ln tanh 1 u + c 2113. ∫ sec h 2 u du = tanh u + c114. ∫ csc h 2 u du = − coth u + c115. ∫ sec h u tanh u du = − sec h u + c116. ∫ csc h u coth u du = − csc h u + c 1 1 ∫ senh u du = senh 2u − u + c 2117. 4 2 1 1118. ∫ cosh 2 u du = senh 2u + u + c 4 2119. ∫ tanh u du = u − tanh u + c 2120. ∫ coth 2 u du = u − coth u + c121. ∫ u senh u du = u cosh u − senh u + c122. ∫ u cosh u du = u senh u − cosh u + c e au123. ∫ e au senh nu du = (a senh nu − n cosh nu ) + c a2 − n2 e au124. ∫ e au cosh nu du = (a cosh nu − n senh nu ) + c a2 − n2

×